Rice response to cadmium bioremediation using sorghum and mycorrhiza (Asian Journal of Agriculture, 2025)
Abstract. Harsono P, Hasanah NAU, Purwanto E, Samanhudi. 2025. Rice response to cadmium bioremediation using sorghum and mycorrhiza. Asian J Agric 9: 522-532. Cadmium (Cd) contamination at 2.9 mg kg-¹ in paddy soils reduces rice productivity and threatens food safety. This study aimed to evaluate the effectiveness of sorghum (Sorghum bicolor) phytoremediation combined with Arbuscular Mycorrhizal Fungi (AMF) in improving rice growth under mild Cd contamination. A factorial randomized complete block design with two cropping systems (seed vs. ratoon, where the same crop is re-grown from the stubble or roots of the first crop) and seven remediation treatments (control; three sorghum varieties (Super 1, Samurai 1, Kawali) combine with/without 10 g AMF plot-¹) was applied in 42 plots (3×4 m). Rice cv. IR 64 was transplanted 30 days after remediation. Significant interactions (p
Keywords: Cadmium contamination, heavy metals, phytoremediation, ratoon cropping system, remediating plants